Dietary Salt-Related Knowledge, Attitudes and Behaviors in Healthy and Hypertensive Turkish Adults from Food Choice Perspective - Burcu Aksoy Canyolu; Beste Özben Sadıç (Foods)
Food choices are influenced by knowledge, attitudes, and behaviors (KABs); therefore, determining KABs regarding salt is a key point for salt reduction, which is a primary public health problem in Turkey. This study aimed to assess salt-related KABs in Turkey. This cross-sectional study was conducted on 415 adults in a hospital in Turkey. A structured questionnaire assessing salt-related KABs was administered, and blood pressure was measured. The majority of participants were aware of the health risks associated with high salt intake. Higher overall attitude scores increased the odds of performing most behaviors to reduce salt, except for checking food labels, using spices instead of salt, and purchasing foods labeled as low-sodium, by almost three-fold. These results suggest that both normotensive and hypertensive adults need to improve their knowledge of the health effects and dietary sources of salt, and how to reduce it. Salt-related KABs were not found to be aligned with all positive attitudes toward salt consumption; this indicates the need for regulations that operate independently of public perceptions, such as policies for reducing salt in the food industry and making reduced-salt products more affordable to encourage healthier food choices.